Principal instructional leadership: a systematic review of China 2014-2024 - Shihui, Hua; Mansor, Azlin Norhaini; Jamaludin, Khairul Azhar (Institute of Advanced Engineering and Science, 2025)
The current research on instructional leadership is predominantly focused on European contexts, with limited studies addressing its application in China. This review aims to explore the instructional leadership practices of Chinese principals, focusing on their unique behaviors and strategies in different urban school contexts. Using the preferred reporting items for systematic reviews and meta-analyses (PRISMA) approach, 483 English-language publications (2014-2024) from five databases: Scopus, Web of Science (WoS), Taylor & Francis, Wiley, and ScienceDirect were analyzed. Deductive thematic analysis focused on three core themes: defining the school mission, managing the instructional program, and developing a positive school climate. The findings reveal that while Chinese principals excel in articulating a clear school mission and vision, they demonstrate limited involvement in curriculum management. These insights underscore the need for targeted professional development to enhance principals’ instructional leadership capacities, particularly in curriculum oversight, to improve teaching quality and student outcomes in China.